Somersault flap 20 years of experience - Lizaraso Caparo, Frank (2022)
We present the results of twenty years old of experience in the use of flap to cover woundseither on determinated areas on the whole surface of the antero-internal side of the tibial region, in order to repair bones and/or metalics plates exposed or chronic wounds of osteomielitis.The characteristics of the flap, viable in all the cases (100 %), depends fundamentally on the base of the puduncle of the flap, that is always bigger than its length, that results advantageous if we talk about legs, where the blood circulation is lower in relation to higher of the body.We enphasases the importance of acting with prudence in front of patients with chronic wounds of the venous system like : post-thrombotic syndromes.We recomended that the «Somersault-Flap», as the ideal option instead of the Cross Leg or «Colgajo Pierna Cruzada» , due to all the problems that this method has and because of being no useful, besides it doesn't solve cases in which the contralateral leg affected, is rigid or if it has been amputated.